Pemodelan Analisis Struktur Menggunakan Aplikasi Berbasis Elemen Hingga: Artikel Review - Warman, Aditya; Arifuddin, Muhammad (Journal of Infrastructure and Construction Technology, 2024)
The rapid advancement of technology has significantly influenced structural engineering, particularly in the design of complex geometries and the analysis of irregular load distributions. Conventional manual calculations often fail to provide precise and reliable results, especially when dealing with large-scale or intricate structural systems. To address these limitations, numerical methods such as the Finite Element Method (FEM) have been developed and widely implemented. FEM divides a structure into smaller elements interconnected through nodal points, enabling detailed analysis of displacements, stresses, and reactions. Alongside theoretical development, FEM has been integrated into computer-based applications that provide more efficient, accurate, and user-friendly tools for structural analysis and design. This paper reviews several widely used FEM-based applications, including SAP2000, ETABS, ANSYS, and ABAQUS. This article utilizes the Literature Review method to review and synthesize findings from four previous studies. Each software offers unique strengths: SAP2000 and ETABS are widely applied in building and general infrastructure design; ANSYS and ABAQUS are well-suited for nonlinear and advanced multiphysics analysis. By comparing these applications, this review confirms the key finding that software specialization (SAP2000/ETABS for infrastructure vs. ANSYS/ABAQUS for advanced non-linear analysis) is crucial. Ultimately, FEM-based applications not only improve the accuracy and efficiency of structural analysis but also enhance safety, reliability, and sustainability in modern construction practices.